Aplicação da Termografia ao Estudo do Comportamento Higrotérmico dos Edifícios - Eva Barreira (2004)
The study of higrothermal behaviour is essential to evaluate the performance of construction components and building envelop. These studies allow the improvement of technical solutions and regulations setting that ensure the durability of the building components and guarantee the users well-being.Most materials and components pathologies are related with temperature action. Therefore, its measuring is necessary to understand the causes of those defects.Infrared thermography can be used to determine the superficial temperature of objects. The detectors collect infrared radiation, turn it into electrical signs and create a thermal image with the distribution of a body superfícial temperature. In this process, each colour expresses a certain range of temperatures.In the present study the ioerating principle of infrared thermography was described, namely in what concerns to theoretical aspects of infrared measuring and external disturbing parameters affecting data collection and interpretation of the results. It was also tested the thermography equipment installed at the Building Physics Laboratory (LFC) of the Faculty of Engineering of the University of Porto (FEUP) and assessed the influence of emissivity and environmental conditions in the measuring.Using infrared thermography it was also studied the wetting process and drying of several materials employed in building construction and analysed the comfort of some floor coatings.KEY-WORDS: Infrared, Thermography, Higrothermal Behaviour, Buildings.